1998
DOI: 10.1126/science.280.5367.1262
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activation of the Phosphatase MKP-3 by ERK2 Mitogen-Activated Protein Kinase

Abstract: MAP kinase phosphatase-3 (MKP-3) dephosphorylates phosphotyrosine and phosphothreonine and inactivates selectively ERK family mitogen-activated protein (MAP) kinases. MKP-3 was activated by direct binding to purified ERK2. Activation was independent of protein kinase activity and required binding of ERK2 to the noncatalytic amino-terminus of MKP-3. Neither the gain-of-function Sevenmaker ERK2 mutant D319N nor c-Jun amino-terminal kinase-stress-activated protein kinase (JNK/SAPK) or p38 MAP kinases bound MKP-3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
430
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 469 publications
(458 citation statements)
references
References 17 publications
19
430
3
Order By: Relevance
“…Jacobs et al (1999) demonstrated that FXFP is an evolutionarily conserved motif that mediates binding of p42 MAPK to various substrate proteins. The discovery that both substrate specificity and tight substrate binding are conferred by the amino terminus of the related phosphatase MKP-3 (Camps et al, 1998;Muda et al, 1998) supports the hypothesis that the FNFP motif within XCL100 mediates its role as a p42 MAPK substrate. In addition, the absence of an analogous experimentally defined JNK docking site (Yang et al, 1998a,b;Jacobs et al, 1999) in XCL100 is consistent with our conclusion that this phosphatase is a poor substrate for JNK.…”
Section: Xcl100 Functions As Both Enzyme and Substrate For P42 Mapkmentioning
confidence: 61%
See 1 more Smart Citation
“…Jacobs et al (1999) demonstrated that FXFP is an evolutionarily conserved motif that mediates binding of p42 MAPK to various substrate proteins. The discovery that both substrate specificity and tight substrate binding are conferred by the amino terminus of the related phosphatase MKP-3 (Camps et al, 1998;Muda et al, 1998) supports the hypothesis that the FNFP motif within XCL100 mediates its role as a p42 MAPK substrate. In addition, the absence of an analogous experimentally defined JNK docking site (Yang et al, 1998a,b;Jacobs et al, 1999) in XCL100 is consistent with our conclusion that this phosphatase is a poor substrate for JNK.…”
Section: Xcl100 Functions As Both Enzyme and Substrate For P42 Mapkmentioning
confidence: 61%
“…Moreover, p42 MAPK may positively regulate XCL100 through at least two other mechanisms: activation of p42 MAPK can induce expression of the closely related phosphatases MKP-1 and MKP-2 (Brondello et al, 1997), and, by analogy to other MKP family members, p42 MAPK may catalytically activate XCL100 by binding to its amino terminus (Camps et al, 1998;Dowd et al, 1998;Fjeld et al, 2000;Chen et al, 2001;Slack et al, 2001). The presence of multiple activation mechanisms may increase the robustness of the p42 MAPK/XCL100 system.…”
Section: Xcl100 Stabilization Confers Negative Feedback Upon P42 Mapkmentioning
confidence: 99%
“…Many dual-specificity phosphatases have been identified that act upon various members of the MAP kinase pathway and are grouped as the MAP kinase phosphatase (MKP) family [45]. Several members can efficiently dephosphorylate p38α and p38β [46,47]; however, p38γ and p38δ are resistant to all known MKP family members. In addition, other types of phosphatases such as serine/ threonine protein phosphotase type 2C (PP2C) has been shown to have a role in downregulating the MAP kinase HOG1 pathway as well as negatively regulating human MKK6 and MKK4 levels in vitro and in vivo [48][49][50][51].…”
Section: Downregulation Of the P38 Signaling Pathwaymentioning
confidence: 99%
“…Recent studies suggest that the N-terminal noncatalytic domain of MKP-3 is responsible for tight binding to its substrates p44-ERK1 and p42-ERK2 . Moreover, MKP-3 is activated by binding to puri®ed ERK2 and this activation is independent of protein kinase activity (Camps et al, 1998). Whether this is a common mechanism for the regulation of other members of the MAP kinase phosphatase family remains to be determined.…”
Section: Binding Of Mkp5 To Endogenous Map Kinasesmentioning
confidence: 99%
“…Nevertheless, recent in vitro studies suggest that MKP-3/PYST1 (Muda et al, 1996a;Mourey et al, 1996;Groom et al, 1996) and M3/6/ hVH-5 (Theodosiou et al, 1996;Martell et al, 1995) are highly selective in inactivating either ERK, or JNK/SAPK and p38 MAP kinases, respectively (Groom et al, 1996;Muda et al, 1996bMuda et al, , 1998. The N-terminal non-catalytic domain of MKP-3 appears to be responsible for binding the ERK2 MAP kinase, thus directing the speci®city of this phosphatase Camps et al, 1998).…”
Section: Introductionmentioning
confidence: 99%